Thermal analysis of slurry ice production system using direct contact heat transfer of carbon dioxide and water mixture - S. Thongwik (2018)
This research studies the heat transfer characteristic during ice formation of a direct contact heat transfer between carbon dioxide and water mixture. This research is divided into two parts. For the first part, the low temperature carbon dioxide, between - 15 and - 60 °C, is injected into water initially at 28 °C and exchanges heat directly. The flow rate of carbon dioxide is varied between 0.003 and 0.017 kg/s while the volume of water is between 1 and 3 L. From the experiment, it is found that the effectiveness of the direct contact heat transfer between the carbon dioxide and the water is closed to 100%. Moreover, the lumped model is found to be used for predicting the temperature of water and the mass of ice formation quite well. However, for this technique, the blockage of ice around the injector always occurs. To avoid this problem, slurry ice is considered instead of pure ice. In the second part of this work, the thermal behavior of the slurry ice by direct contact heat transfer technique between carbon dioxide and water mixture is investigated. Compressor oil and Tween 60 are mixed with water for making slurry ice and it is found that the suitable composition is water/oil/Tween 60 at 100/6/1 by volume. Again, the lumped model can be used for predicting the temperature of water mixture and the mass of slurry ice quite well. © 2008 Elsevier Ltd. All rights reserved.